Pengaruh Consumer E-Sports Engagement terhadap Consumption Behaviour Pemain E-Sports - Kenzie, Muhammad Hisyam Maulana; Arafah, Willy (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the impact of Consumer Electronic Sports Engagement (CeSE) on the consumption behavior of eSports players. The study involved 120 respondents who are actively engaged in eSports activities. The findings indicate that engagement in electronic sports has a significant influence on the consumption behavior of eSports players. Several variables are affected by the level of electronic sports engagement, including purchase intention, community engagement, co-production, recruitment, and word-of-mouth. Specifically, the study found that Consumer Electronic Sports Engagement significantly affects purchase intention, community engagement, co-production, recruitment, and word-of-mouth. These findings suggest that engagement in electronic sports plays a crucial role in shaping various aspects of eSports players' consumption behavior. Therefore, a deeper understanding of Consumer Electronic Sports Engagement can assist marketers and eSports developers in designing more effective strategies to attract and retain their player base. Keywords: Consumer Electronic Sports Engagement, Consumption Behavior, Community Engagement, Co-Production, Esports, Purchase Intention, Recruitment, Word-Of-Mouth